2014
DOI: 10.1161/strokeaha.114.006448
|View full text |Cite
|
Sign up to set email alerts
|

Number of Cerebral Microbleeds and Risk of Intracerebral Hemorrhage After Intravenous Thrombolysis

Abstract: Background and Purpose-Cerebral microbleeds (CMBs) are found in a substantial proportion of patients with ischemic stroke eligible for treatment with intravenous thrombolysis. Until now, there is limited data on the impact of multiple CMBs on occurrence of intracerebral hemorrhage (ICH) after intravenous thrombolysis. Methods-Between 2008 and 2013, all patients receiving MRI-based intravenous thrombolysis were identified within our prospective thrombolysis register. Number of CMBs was rated on pretreatment T2*… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
62
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 91 publications
(67 citation statements)
references
References 37 publications
(56 reference statements)
2
62
0
3
Order By: Relevance
“…Using multilevel mixed-effects logistic regression, we investigated associations of pre-treatment CMB presence, burden (1, 2-4, ≥5, and >10), and presumed pathogenesis (cerebral amyloid angiopathy defined as strictly lobar CMBs and noncerebral amyloid angiopathy) with symptomatic ICH, parenchymal hematoma (within [parenchymal hemorrhage, PH] and remote from the ischemic area [remote parenchymal hemorrhage, PHr]), and poor 3-to 6-month functional outcome (modified Rankin score >2). We performed a large-scale pooled individual patient data meta-analysis of quality observational studies to test the following hypotheses: (1) there is a relationship between increasing CMB burden and ICH risk 8,9 ; (2) strictly lobar CMBs (reflecting possible or probable cerebral amyloid angiopathy [CAA]) and mixed or strictly deep CMBs (likely associated with hypertensive arteriopathy) have different effects on ICH risk; (3) CMBs are associated more strongly with the risk of remote ICH than other ICH types 10 ; and (4) CMBs are associated with worse functional outcome. …”
mentioning
confidence: 99%
“…Using multilevel mixed-effects logistic regression, we investigated associations of pre-treatment CMB presence, burden (1, 2-4, ≥5, and >10), and presumed pathogenesis (cerebral amyloid angiopathy defined as strictly lobar CMBs and noncerebral amyloid angiopathy) with symptomatic ICH, parenchymal hematoma (within [parenchymal hemorrhage, PH] and remote from the ischemic area [remote parenchymal hemorrhage, PHr]), and poor 3-to 6-month functional outcome (modified Rankin score >2). We performed a large-scale pooled individual patient data meta-analysis of quality observational studies to test the following hypotheses: (1) there is a relationship between increasing CMB burden and ICH risk 8,9 ; (2) strictly lobar CMBs (reflecting possible or probable cerebral amyloid angiopathy [CAA]) and mixed or strictly deep CMBs (likely associated with hypertensive arteriopathy) have different effects on ICH risk; (3) CMBs are associated more strongly with the risk of remote ICH than other ICH types 10 ; and (4) CMBs are associated with worse functional outcome. …”
mentioning
confidence: 99%
“…SCAA appears to be an important differential diagnosis in patients with progressive neuropsychiatric symptoms and executive impairment [17,18,41]. The diagnosis of SCAA is crucial and can have essential therapeutic consequences with regard to thrombolytic or anticoagulation therapy [42,43] blood pressure control [44] and prognosis due to their risk of further spontaneous brain hemorrhages and consequent dementia [45]. MRI depicting vascular lesions currently represents the best disease marker of SCAA [46].…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] One study showed a higher risk of symptomatic hemorrhage after intravenous thrombolysis in patients with Ͼ5 microbleeds but no association with less favorable outcome. 17 More studies to assess the safety and effectiveness of thrombolysis in patients with microbleeds are needed.…”
Section: Multimodal Ct As An Effective Screening Tool For Acute Strokmentioning
confidence: 99%